Leptin Induces Proadipogenic and Proinflammatory Signaling in Adipocytes - Palhinha, Lohanna; Liechocki, Sally; Hottz, Eugenio D.; Pereira, Jéssica Aparecida da Silva; de Almeida, Cecília J.; Moraes-Vieira, Pedro Manoel M.; Bozza, Patrícia T.; Maya-Monteiro, Clarissa Menezes (Frontiers in Endocrinology, 2019)
Background: Leptin is an adipokine with well-known effects on the central nervous system including the induction of energy expenditure and satiety. Leptin also has major relevance when activating immune cells and modulating inflammatory response. In obesity, increases in white adipose tissue accumulation and leptin levels are accompanied by hypothalamic resistance to leptin. Even though the adipose tissue is a leptin-rich environment, leptin’s local actions regarding adipogenesis were not thoroughly investigated until now. Here we evaluate the contributions of leptin’s direct signaling in preadipocytes and adipose tissue-derived stromal cells (ASCs) for adipogenesis. Methods: Adipocytes were differentiated from the murine lineage of preadipocytes 3T3-L1 or ASCs from subcutaneous and visceral (retroperitoneal) fat depots from C57Bl/6J mice. Differentiating cells were treated with leptin in addition to or in replacement of insulin. The advance of adipogenesis was assessed by the expression and secretion of adipogenesis- and lipogenesis-related proteins by Western blot and immunoenzimatic assays, and the accumulation of lipid droplets by fluorescence microscopy. Results: Leptin treatment in 3T3-L1 preadipocytes or ASCs increased the production of the adipogenesis- and lipogenesis-related proteins PLIN1, CAV-1, PPARγ, SREBP1C and/or adiponectin at earlier stages of differentiation. In 3T3-L1 preadipocytes, we found that leptin induced lipid droplets’ formation in an mTOR-dependent manner. Also, leptin promoted the enhancement of TNF-α and reduction of IL-10 secretion, indicating that it induces a proinflammatory cytokine profile in 3T3-L1 adipocytes. Since insulin is considered an essential factor for preadipocyte differentiation, we asked whether leptin would support adipogenesis in the absence of insulin. Importantly, leptin induced the formation of lipid droplets and the expression of adipogenesis-related proteins independently of insulin during the differentiation of 3T3-L1 cells and ASCs. Conclusions: Our results demonstrate that leptin induces intracellular signaling in preadipocytes and adipocytes promoting adipogenesis and modulating the secretion of inflammatory mediators. Also, leptin restores adipogenesis in the absence of insulin. These findings contribute to the understanding of leptin’s local signaling in precursor and mature adipose cells. The proadipogenic role of leptin unraveled here may be of especial relevance during obesity, when its central signaling is defective.